The Relationship Behavior Survey: A Comprehensive Measure of Psychological Intimate Partner Violence for Adolescents - Cascardi, Michele (Journal of interpersonal violence, 2023)
Commonly used scales of psychological intimate partner violence (ψIPV) for adolescents may not include sufficient items to measure adequately different forms of ψ aggressive behaviors. They may also characterize as harmful ψ aggressive behaviors occurring in non-conflictual or joking contexts. The current study examined a new scale, the Relationship Behavior Survey (RBS), which was designed to measure three different forms of ψIPV (denigrating, controlling, and intrusive behaviors) and the appraisals of the perpetrator’s intent. Factor structure was examined, and incremental validity was tested by examining the relation of the RBS to general aggressive tendencies and physical IPV after accounting for the emotional abuse and threatening behavior subscales of the Conflict in Adolescent Dating Relationships Inventory (CADRI). Criterion validity and gender differences were also examined. Data were collected using an online survey from a national sample of 1,100 13 to 17-year-olds in the United States (51% identified as female, 80% as White) in a dating relationship. Confirmatory factor analysis supported one ψIPV construct for males and females. The RBS demonstrated incremental validity; criterion validity was supported for controlling intent for males and females and mistrust intent for females. Joking intent was the most reported intent for males and correlated unexpectedly with physical IPV. The RBS captures a larger range of ψIPV behaviors than the CADRI. The addition of intent appraisals provides important information to differentiate forms of ψIPV, particularly in relation to acts motivated by coercion and mistrust.